Determination of Trace Copper in Drinking Water by Flame Atomic Absorption Spectrometry After Solid Phase Extraction on Polymer Modified Silica Gel - Chen, Jing; Wang, Ning; Li, Bo; Wan, Dongjin; Sun, Xuzhuo (Asian Journal of Chemistry, 2013)
Silica gel was chemically modified by a polymer containing thiol group and used as a solid phase extraction adsorbent for the determination of trace copper in drinking water samples by flame absorption spectrometry. The effects of pH, sample flow rate and volume, elution conditions and concomitant ions on the recovery of the analyte were investigated. The results showed that copper could be adsorbed at pH 6 and eluted by 4 mL HCl solution (0.5 mol L-1). Under the optimized conditions, the adsorption capacity of modified silica gel was found to be 3.7 mg g-1 for copper. The detection limit of the proposed method was 1.3 ng mL-1 for copper with an enrichment factor of 18.7. The analytical result for the certified reference water sample(GBWE080081) was in a good agreement with the certified value. The proposed method has also been successfully applied to the determination of trace copper in boiled water, purified water and mineral water with the recoveries for spiked samples between 96 and 103 %.